Adaptability of the metal(iii, iv) 1, 2, 3-trioxobenzene rod secondary building unit for the production of chemically stable and catalytically active MOFs. Issue 54 (23rd June 2017) - Mouchaham, Georges; Abeykoon, Brian; Giménez-Marqués, Mónica; Navalon, Sergio; Santiago-Portillo, Andrea; Affram, Maame; Guillou, Nathalie; Martineau, Charlotte; Garcia, Hermenegildo; Fateeva, Alexandra; Devic, Thomas
Abstract : Metal-1, 2, 3-trioxobenzene rod secondary building units are robust enough to adapt to cations of various charges. Abstract : The use of a 5, 10, 15, 20-tetrakis(3, 4, 5-trihydroxyphenyl)porphyrin has yielded a new MOF based on M-1, 2, 3-trioxobenzene chains that can be made of M = Zr(iv ) or RE(iii ) (RE = rare earth), showing a very high and limited chemical stability, respectively. The robust metallated Zr-analogue, Co-MIL-173(Zr), has proven to be a heme-like heterogeneous catalyst suitable for aerobic oxidation of hydrocarbons.